PHYSICAL EXERCISE TECHNIQUES - Khasanov, Anvar Takhirovich; Ganiyeva , Saida (Innovative Development in Educational Activities, 2024)
This article provides an overview of exercise theory based on pedagogical tasks and provides feedback on the teacher’s options for choosing the most effective exercise.